Study of pulmonary function tests in response to localized cold stimuli in age group between 19-30 years of Guwahati city - Dutta, Bijit; Bora, Bonti (International Journal of Research in Medical Sciences, 2017)
Background: The aim of the study was to observe any variation in the pulmonary functions in response to localized cold stimuli in an externally controlled environment. Methods: The baseline pulmonary function parameters were obtained before the introduction of localized cold stimuli. Now the stimuli were introduced by immersing both feet up to ankle in a bucket full of cold water maintained at temperature between 8-10degree Celsius in 30 male healthy subjects (age group 19-30 years) and the parameters were noted after 2 minutes and 5 minutes respectively using a Medspiror (HELIOS) Electronic spirometer and keeping room temperature at 24ocelsius in the Department of Physiology, Gauhati Medical College, Guwahati, Assam, India. For statistical analysis, the value of the pulmonary function parameters were presented as Mean±standard deviation. Analysis of variance (ANOVA) using Statistical Package for Social Sciences (SPSS) version 20 was employed for comparing the parameters and p<0.05 was considered as significant. Results: It was observed that the tidal volume and Inspiratory capacity showed a significant increase (p<0.05) whereas the Inspiratory reserve volume, expiratory reserve volume and forced vital capacity showed a significant decrease (p<0.05) in response to the cold stimuli. Conclusions: A significant effect was obtained in the pulmonary function tests exposed to cold stimuli showing the multidimensional response of the respiratory mechanics to cold, making a base for further information into the cold climatic effect in an individual.